Fruit Growth and Oil Accumulation of Olive (Olea europaea L.) Cultivars at Different Locations Along a Latitudinal–Altitudinal Gradient - Leila M. Hamze; María Cecilia Rousseaux; Peter S. Searles; Eduardo R. Trentacoste (Horticulturae)
Environmental conditions during olive fruit development and genotype have shown to be important sources of variability in final fruit weight and oil concentration. There are fewer studies concerning how the environment and genotype modulate growth dynamics. Thus, the present study aimed to evaluate the timing of fruit growth, pit hardening, and oil accumulation in several olive cultivars under different air temperatures along a latitudinal gradient (29°–33° S) with a range of altitudes (450–1250 masl) in Western Argentina; determine parameters derived from the dynamics of fruit growth and oil accumulation along the same gradient; and explore possible relationships between derived parameters and air temperatures. The cultivars evaluated were Arbequina, Arbosana, Coratina, Changlot, and Picual. Pit hardening occurred 20 days earlier in warmer locations, leading to an earlier onset of oil synthesis. The final fruit dry weight was mainly influenced by the cultivar, which was explained by differences in fruit growth rates. Cooler locations had 39% higher average final fruit dry weight and 22% higher oil concentration than warmer ones. Differences in final oil concentration between genotypes × environments were primarily associated with the oil accumulation rate rather than the duration of the oil accumulation period. However, changes in this rate seem to be cultivar-dependent. Interestingly, the rate and oil accumulation duration showed a negative relationship. These results highlight the need to explore genetic variability in temperature response to limit the detrimental impacts of global warming on olive fruit growth and oil concentration.